Investigation and control of measles outbreak in the Hong Kong International Airport, 2019 - Chi Hong Wong; Wing Hang Lam; Ho Yeung Lam; Tsz Sum Lam; Lei Ming Raymond Ho; Yiu Hong Leung; Chau Kuen Yonnie Lam; Shuk Kwan Chang (World Health Organization Regional Office for the Western Pacific, 2020)
Introduction: Hong Kong SAR (China) achieved measles elimination status in 2016, and the incidence of measles infection had been low over the past few years. However, the Centre for Health Protection (CHP) at the Department of Health was notified on 22 March 2019 of an outbreak of three cases of measles infection among workers at the Hong Kong International Airport (HKIA). Methods: We reviewed notifications of measles received by CHP from 1 January to 17 May 2019. We defined a confirmed case of measles as having laboratory evidence of measles infection. All confirmed cases among airport workers or those with epidemiological information suggesting they had been infected by contact with airport workers were included in the review. We described the epidemiological features and reviewed the control measures against the outbreak. Results: We identified 33 cases, 29 of which were among airport workers. They comprised 22 men and 11 women, aged 20-49 years (median 25 years). The majority of people with confirmed measles presented with fever and rash. All required hospitalization. None developed complications. Control measures, including enhanced environmental hygiene and improved ventilation at HKIA and vaccinations for the airport community, were implemented. Vaccinations were provided to 8501 eligible airport workers, and the outbreak was declared over on 17 May 2019. Discussion: Early recognition of the outbreak and prompt control measures, especially targeted vaccination of the exposed population, effectively controlled the outbreak in just two weeks.